2016
DOI: 10.3847/1538-4357/833/2/158
|View full text |Cite
|
Sign up to set email alerts
|

The Information Content of Stellar Halos: Stellar Population Gradients and Accretion Histories in Early-Type Illustris Galaxies

Abstract: Long dynamical timescales in the outskirts of galaxies preserve the information content of their accretion histories, for example in the form of stellar population gradients. We present a detailed analysis of the stellar halo properties of a statistically representative sample of early-type galaxies from the Illustris simulation and show that stellar population gradients at large radii can indeed be used to infer basic properties of galactic accretion histories. We measure metallicity, age, and surface-brightn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
96
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 105 publications
20
96
0
Order By: Relevance
“…Greene et al 2015;McDermid et al 2015; Barone et al 2018;Ferreras et al 2019). This is consistent with the cosmological simulations of the massive ETGs that predict different metallicity profiles as function of the mass assembly history, with shallower profiles in the outskirts when repeated mergers occur (Cook et al 2016).…”
Section: Introductionsupporting
confidence: 90%
“…Greene et al 2015;McDermid et al 2015; Barone et al 2018;Ferreras et al 2019). This is consistent with the cosmological simulations of the massive ETGs that predict different metallicity profiles as function of the mass assembly history, with shallower profiles in the outskirts when repeated mergers occur (Cook et al 2016).…”
Section: Introductionsupporting
confidence: 90%
“…The CRC in NGC 3522 has a peak rotation of only about 20 km/s and is located within the central 5 tions (e.g. Dubois et al 2013;Hirschmann et al 2015;Cook et al 2016) Notwithstanding the details and the absolute level of predicted metallicity gradients by models, a general conclusion is that galaxies undergoing dissipation-less merging will have flatter gradients than galaxies that experience gas-rich mergers or secondary star formation of any origin. This is important because we can link these predictions with formation scenarios for galaxies with cores (gas-poor major mergers) or for those with core-less light profiles (gas-rich mergers followed by a nuclear starburst).…”
Section: Formation Of Flat Metallicity Gradientsmentioning
confidence: 99%
“…Massive galaxies are gas-poor systems, and their late evolution (z < 2) is dominated by accretion of stars formed elsewhere (e.g. De Lucia & Blaizot 2007;Oser et al 2010;Wellons et al 2015;Cook et al 2016;Lagos et al 2018). The current picture is that low-mass galaxies typically grow through star formation and are more likely to experience dissipative mergers, while massive galaxies accrete stars formed elsewhere and grow through dissipation-less mergers (e.g.…”
Section: Formation Of Slow Rotators With and Without Coresmentioning
confidence: 99%
“…The simulation features a physical model of galaxy formation (Vogelsberger et al 2013;Torrey et al 2014) which has been shown to reproduce various galaxy observables, including several which were not used in the calibration of the model (e.g. Sales et al 2015;Wellons et al 2015;Rodriguez-Gomez et al 2015;Genel et al 2015;Mistani et al 2016;Cook et al 2016).…”
Section: The Illustris and Illustris-dark Simulationsmentioning
confidence: 99%